Distance Learning of Foreign Languages for Students of Economic Specialties. - Petrenko, Oksana; Hnatyshena, Iryna; Khariuk, Inna; Azarova, Inessa; Ivanytska, Iuliia (Journal of Higher Education Theory and Practice, 2022)
The purpose of the present research is a comprehensive analysis of the process and results of distance learning of a foreign language (English) for students of economic specialties. The research methods are as follows: the analysis of modern opportunities for organizing distance learning; study of theoretical and methodological papers on the subject matter; method of experimental teaching of foreign languages with an emphasis on tactics of stimulating the personal and motivational sphere of students’ educational activities; development of author’s diagnostic models in order to reveal the dynamics of development of knowledge and practical skills in a foreign language of students of economic profile; qualitative and quantitative analysis of empirical data; statistical and mathematical interpretation of results, their functional analysis; method of generalization and abstraction. According to the data obtained, the hypothesis of the research has been confirmed. It lies in the fact that the students with higher indicators of motivation have shown higher results of academic achievements in mastering a foreign language.
Keywords: higher education, online education, English learning, teaching model, communicative competence, motivation